2020
DOI: 10.1002/hyp.14001
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and spatio‐temporal hot spots in an effluent‐dominated urban river

Abstract: In arid and semi-arid regions, many rivers experience extremely low flow conditions during seasonal dry periods. During these times, effluent from wastewater treatment plants can make up the majority of flow in the river. However, water quality in urban systems can also be strongly influenced by the natural or human-influenced flow regime and discharge from other anthropogenic sources such as industrial operations and runoff from impervious surfaces. In this study, we aimed to determine whether water quality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 59 publications
2
24
1
Order By: Relevance
“…If a sub-reach had insufficient solutions (i.e., less than 100 solutions) for Q gw , Q sw , and Q out , boxplots are not shown. Urban and agricultural areas are a complex system of human-built systems that interact and interfere with underlying natural surface water and groundwater flowpaths (Kendy & Bredehoeft, 2006;Schliemann et al, 2021). As discussed in Cook (2013), the accuracy of the mass balance methods applied here are dependent on the ability to distinguish concentration ranges for different source categories and as discussed in Aubert et al (2013), the observed concentrations of different ions can be time and flow dependent for a given sampling location.…”
Section: Flow and Mass Balancesmentioning
confidence: 99%
“…If a sub-reach had insufficient solutions (i.e., less than 100 solutions) for Q gw , Q sw , and Q out , boxplots are not shown. Urban and agricultural areas are a complex system of human-built systems that interact and interfere with underlying natural surface water and groundwater flowpaths (Kendy & Bredehoeft, 2006;Schliemann et al, 2021). As discussed in Cook (2013), the accuracy of the mass balance methods applied here are dependent on the ability to distinguish concentration ranges for different source categories and as discussed in Aubert et al (2013), the observed concentrations of different ions can be time and flow dependent for a given sampling location.…”
Section: Flow and Mass Balancesmentioning
confidence: 99%
“…Dry-weather flows, or urban drool, derives primarily from "nuisance" flows (e.g., overirrigation of ornamental landscaping and turf, car washes, street cleaning, irrigation return flows), permitted and illicit point sources of discharge (e.g., discharges from industrial, construction, and dewatering operations), domestic wastewater and drinking water infras-tructure leaks or overflow, "natural" non-urban water flowing from outlying areas, and groundwater inflows [8,9,11,12,16,17,24,33,34]. The most predominant sources of nonpoint dry-weather flow in semi-arid climates include irrigation return flow and shallow groundwater contributions.…”
Section: Urban Drool: Dry-weather Urban Water Qualitymentioning
confidence: 99%
“…The South Platte River flows through Denver, Colorado and represents a source of recreation for people, habitat for aquatic life, and a supply of drinking water for Denver and downstream communities [23]. Similar to many urban waterways, urban processes and drainage within the city severely impair the river's water quality [24]. This metropolitan area is situated in a semi-arid climate and, similar to many urban waterways in the western United States, the South Platte River is dominated by wastewater effluent during periods of dry-weather [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations